Effect of Cyclic Change in Temperature in Solid Phase on the Viability of Cryopreserved Rats Hepatocytes - Lebedinskiy, A. S.; Zinchenko, A. V.; Petrenko, A. Yu.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2002)
The effect of cyclic change in temperature within various ranges (77÷223, 77÷173 and 77÷123 K) on the viability of isolated rat’s hepatocytes was investigated. The possibility of their transportation at the temperature of dry ice (194.5 K) was estimated.